Sharia E-Wallet: The Issue of Sharia Compliance and Data Protection - Muhammad Khaeruddin Hamsin; Abdul Halim; Rizaldy Anggriawan; Hilda Lutfiani (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
Sharia digital payments have lately emerged as one of the most significant innovations and breakthroughs in the field of Islamic economics in Indonesia. However, behind the positive side of the use of sharia e-wallets, there is one thing that all parties involved need to pay attention to, which if ignored can become a double-edged sword for its users, namely compliance, security, and personal data protection. The paper aims to investigate how the Indonesian government regulates data privacy for Islamic e-wallet users. It also investigates the potential risks and challenges of Islamic digital payments particularly in regard to data protection. Besides, it also investigates whether or not the sharia e-wallet has complied with the Fatwa of National Sharia Council (DSN-MUI). The study used normative research methods employing statutory, case, and conceptual approaches. This study reveals that the use of sharia e-wallets in Indonesia is essentially in compliance with Islamic principles as stated in the Fatwa of the National Sharia Council. As for the protection of personal data, in fact, this has been regulated in a comprehensive manner by the government and related state institutions such as Bank Indonesia and the Financial Services Authority. However, the government still has work that must be considered in regard to the compliance of sharia digital payment operators with established laws and regulations, where in the event of the operators violated the use of data privacy, thus they will face a severe sanctions stipulated by the prevailed rule.